The Universality of IHL – Surmounting the Last Bastion of the Pacific - Thynne, Kelisiana (Victoria University of Wellington Law Review, 2010)
In a special edition of the VUWLR on the 60th anniversary of the four Geneva Conventions of 1949, it is timely to reflect on the achievements that have come about in the Pacific region, and why this is a cause for celebration. Nonetheless, there are other major international humanitarian law (IHL) instruments developed in the last 60 years which are yet to achieve universal ratification. In the Pacific, in particular, it is often difficult to demonstrate how IHL is relevant. This article addresses the challenges that the Pacific region poses in terms of IHL ratification and discusses how IHL instruments are indeed pertinent to the Pacific context, focusing on the three Additional Protocols to the Geneva Conventions, the Convention on the Prohibition of Anti-Personnel Mines and the Rome Statute of the International Criminal Court. It concludes that in the Pacific these challenges should be seen as opportunities to address historical and current problems associated with war and that, by the next major anniversary, the Pacific might be, if not leading the way, at least not lagging behind.